Determining the influence of surface energy of polymer films on the wetting and adhesion of flexographic inks - Slobodianyk, Valentyna; Koniukhova, Ivanna (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the process of wetting and adhesive interaction between flexographic inks and polymer films of different nature and surface structure. An issue related to flexographic printing on polymer films is insufficient surface wettability and low stability of adhesion of the ink layer, which worsens the print quality. This work explores the wetting of the surface of films with liquids of different polarity and with UV flexographic ink. The equilibrium values of the cosine of the wetting angle for non-polar and polar liquids have been experimentally determined. The cosθ values for non-polar liquids are 0.90–0.99, while for polar liquids they decrease to 0.36–0.92 depending on the type of film surface. The thermodynamic characteristics of wetting, in particular the work of adhesion and cohesion, were calculated. It was established that the work of adhesion varies within 45–140 mN/m. It has been shown that wetting is determined by the ratio of the dispersive and polar components of surface energy. For non-polar liquids, dispersive interactions dominate, while for polar liquids, polar ones. The influence of the structural characteristics of the surface on wetting has been established. The matte polypropylene film is characterized by worse wettability compared to glossy samples. The components of the surface energy were determined by the Owens-Wendt method, which made it possible to establish their influence on adhesive interaction. The surface energy values of polymer films are 42–53 mN/m, while the proportion of the polar component increases to 0.19 for samples with better wettability. It has been shown that the adhesive behavior of UV flexographic ink is comparable to polar liquids. The results could be used to predict the wetting of polymer materials and to optimize flexographic printing processes